TANTANGAN IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SGDs) DI INDONESIA - Mirna Amirya; Gugus Irianto (Universitas Islam Negeri Alauddin Makassar, 2023)
The Sustainable Development Goals (SDGs) reflect ambitious development goals with a transformative vision. A new development agenda creates a holistic development framework. Experts predict the new agenda could be successful. The SDGs bring great opportunities for developing countries, including Indonesia, but also great challenges. This study explores key challenges of implementing the SDGs in Indonesia. Data collection techniques using literature review. The secondary data are used in the form of relevant research journals. Analysis was conducted by identifying challenges in implementing the SDGs. The results present several challenges, namely First, Aligning the SDGs with national and regional development planning, Second, Increasing vertical and horizontal coordination; and Third, Increasing stakeholder participation. The implications of this research help to increase awareness and understanding of various interested parties regarding the implementation of the SDGs and their challenges in Indonesia and mitigate these challenges. Keywords : Development plans, Implementation challenges, Indonesia Government, SDGs